Target-site mediated insecticide resistance in major mosquito (Diptera: Culicidae) vectors: A systematic review - Subhajit Das; Abhirup Saha; Prapti Das; Debayan Raha; Dhiraj Saha (Asian Pacific Journal of Tropical Medicine)
The use of insecticides remain the most effective vector control approach for mosquito borne diseases like malaria, dengue fever, chikungunya, and Zika virus disease; however, their increasing resistance has complicated the management. Mutations in kdr, ace-1/ace-2, rdl, and nAChR, are involved in target-site mediated resistance and prevent the binding of pyrethroids and dichlorodiph enyltrichloroethane, organophosphorus pesticide, carbamates and cyclodienes, respectively. Here, we review the current knowledge on target-site mediated insecticidal resistance mechanisms in major mosquito vectors and the techniques used to identify these mutations. The results showed that kdr mutations are frequently reported in mosquito species, indicating the overuse of pyrethroid in mosquito control. Report on ace mutations is very limited, primarily detected in Anopheles and Culex, with extremely low detection rate in Aedes, despite the wide application of organophosphates in their control. Notably, reports of rdl mutations and changes in nAChR are rare, which provides an opportunity to exploit these target sites, particularly in the event of disease outbreaks. Among various detection methods such as RFLP, TaqMan, Multiplex PCR and FRET, allele-specific PCR is mostly employed, especially in detecting kdr mutation. However, allele-specific PCR cannot detect novel mutation. As a result, there is an urgent need to develop a scalable, cost-effective tool that can be widely applied especially as these mutations are genetic markers for early detection of insecticide resistance. Robust monitoring methods remain critical to manage insecticide resistance and effective control of mosquito-borne diseases.